Phthalates and diet: a review of the food monitoring and epidemiology data - Serrano, Samantha E (BioMed Central, 2014)
Phthalates are associated with a variety of health outcomes, but sources that may be targeted for exposure reduction messaging remain elusive. Diet is considered a significant exposure pathway for these compounds. Therefore, we sought to identify primary foods associated with increased exposure through a review of the food monitoring survey and epidemiological data. A search in PubMed and Google Scholar for keywords "phthalates" and "diet" "food" "food stuffs" "dietary intake" "food intake" and "food concentration" resulted in 17 studies measuring phthalate concentrations in United States (US) and international foods, three epidemiological association studies, and three interventions. We report on food groups with high (≥300 μg/kg) and low (<50 μg/kg) concentrations and compare these to foods associated with phthalate body burden. Based on these data, we estimated daily intakes of di-2-ethylhexyl phthalate (DEHP) of US women of reproductive age, adolescents and infants for typical consumption patterns as well as healthy and poor diets. We consistently observed high DEHP concentrations in poultry, cooking oils and cream-based dairy products (≥300 μg/kg) across food monitoring studies. Diethyl phthalate (DEP) levels were found at low concentrations across all food groups. In line with these data, epidemiological studies showed positive associations between consumption of meats, discretionary fat and dairy products and DEHP. In contrast to food monitoring data, DEP was found to be associated with intake of vegetables in two studies. DEHP exposure estimates based on typical diets were 5.7, 8.1, and 42.1 μg/kg-day for women of reproductive age, adolescents and infants, respectively, with dairy as the largest contributor to exposure. Diets high in meat and dairy consumption resulted in two-fold increases in exposure. Estimates for infants based on a typical diet exceeded the Environmental Protection Agency’s reference dose of 20 μg/kg-day while diets high in dairy and meat consumed by adolescents also exceeded this threshold. The review of the literature demonstrated that DEHP in some meats, fats and dairy products is consistently found in high concentrations and can contribute to exposure. Guidance on future research in this area is provided that may help to identify methods to reduce dietary phthalate exposures.